Emergency Peripartum Hysterectomy at a Tertiary Care Hospital: A Five Year Analysis - Rana, Shraddha; Kattel, Pramod; Prasad Deep, Jagat (Nepal Journal of Obstetrics and Gynaecology, 2020)
Aims: To analyze the medical records of emergency peripartum hysterectomy in a teaching hospital Methods: A hospital based descriptive cross-sectional study was carried out on emergency peripartum hysterectomy at National Medical College and Teaching Hospital, Birgunj, Nepal from July 2011 to July 2016. Data were collected from the medical record. Results: There were 29 maternal survivors out of 33 cases of emergency peripartum hysterectomy, among which 21 cases were of subtotal and rest 11 had undergone total hysterectomy. The incidence of emergency peripartum hysterectomy was found out to be 0.2%. Most of the women who had undergone hysterectomy were of high parity (≥4) and advanced maternal age. Mean age of hysterectomy was 27 years. Major indications for hysterectomy were uterine rupture (n=13, 40%) followed by uterine atony (n=11, 33%), placental complications (n=8, 24%) and uterine inversion (n=1, 3%). Three-fourth of women who underwent hysterectomy for placental complications had history of previous caesarean section. Emergency peripartum hysterectomy following caesarean section was 19 (57.6%) and the rest 14 (42.4%) had delivered vaginally. Twenty-six women (79%) were referred-in cases. Conclusions: Majority (88%) of peripartum hysterectomies were maternal near-miss and resulted in mortality of 12%. Uterine rupture and atony constituted almost three-fourth of cases and emergency procedure was in rising trend each year over five years of record. Keywords: caesarean section, peripartum hysterectomy, postpartum haemorrhage